Interaction Between Intrinsic Renal Cells and Immune Cells in the Progression of Acute Kidney Injury - Deng, Junhui; Wu, Zhifen; He, Yun; Lin, Lirong; Tan, Wei; Yang, Jurong (Frontiers in Medicine, 2022)
A growing number of studies have confirmed that immune cells play various key roles in the pathophysiology of acute kidney injury (AKI) development. Various immune cell subsets reside in the kidney, including macrophages, dendritic cells, neutrophils, lymphocytes, and NK cells. During AKI, tissue-resident immune cells interact with tubular epithelial cells (TECs), endothelial cells, and podocytes in the kidney to form a dynamic immune microenvironment that determines AKI severity and the progression of fibrosis. Injuries such as ischemia and hypoxia, and exposure to drugs or toxins can trigger a widespread inflammatory response in the kidney. The production of chemokines and cytokines by both renal cells and resident immune cells leads to the recruitment and infiltration of various immune cell types in the kidney that promote programmed cell death and phenotypic transformation of renal cells, ultimately leading to renal impairment and fibrosis. Innate immune cells, especially macrophages, play an important role in the pathophysiology of AKI through alternative polarization phenotypes and inhibition of renal cell cycle arrest. Herein, we will provide an overview of the current literature discussing the interplay between resident renal cell and immune cell interactions, and how these interactions contribute to the pathogenesis of AKI.